2019
DOI: 10.1016/j.joca.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

CD146/MCAM distinguishes stem cell subpopulations with distinct migration and regenerative potential in degenerative intervertebral discs

Abstract: Objective: This study aimed to characterize the mesenchymal stem cell (MSC) subpopulation migrating towards a degenerated intervertebral disc (IVD) and to assess its regenerative potential. Design: Based on initial screening for migration towards CC motif chemokine ligand 5 (CCL5), the migration potential of CD146þ and CD146-mesenchymal stem cells (MSCs) was evaluated in vitro and in a degenerated organ culture model (degeneration by high-frequency loading in a bioreactor). Discogenic differentiation potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 53 publications
(48 reference statements)
1
59
0
Order By: Relevance
“…Several earlier organ culture studies have demonstrated migration of exogenously applied MSCs through the endplate into the IVD. [5][6][7][8] Although bovine IVDs have been used for those studies, results of the present work showed that MSCs could migrate through the endplate into an intact human IVD ( Supplementary Fig. 2, http://links.lww.com/ BRS/B443).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Several earlier organ culture studies have demonstrated migration of exogenously applied MSCs through the endplate into the IVD. [5][6][7][8] Although bovine IVDs have been used for those studies, results of the present work showed that MSCs could migrate through the endplate into an intact human IVD ( Supplementary Fig. 2, http://links.lww.com/ BRS/B443).…”
Section: Discussionmentioning
confidence: 64%
“…Migration of exogenously delivered bone marrowderived MSCs through the endplate into the IVD has been described as an alternative approach for intradiscal cell application in several whole IVD organ culture models. [5][6][7][8] Hereby, MSC migration through the IVD tissue was enhanced in IVDs cultured under degeneration-inducing conditions. 5 The homed MSCs were shown to promote matrix remodeling, whereby more sustained effects are expected by cell homing compared to injection of potentially unphysiological sources and numbers of cells.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…For example, the expression of CD146-also known as melanoma cell adhesion molecule (MCAM)-was downregulated in MSCs derived from aged donors compared to those from young donors, as well as in MSCs after prolonged in vitro expansion (Gnani et al, 2019). Furthermore, low but not high CD146 expression was associated with a senescent phenotype in MSCs (Jin et al, 2016), and CD146 + MSCs showed increased migratory potential toward degenerating tissues (Wangler et al, 2019). CD264 is another surface marker of in vitro aging in MSCs that is unrelated to the chronologic age of the donor (Madsen et al, 2017); cells expressing this protein exhibit increased senescence-associated β-galactosidase (SA-β-gal) activity and reduced differentiation potential and colony-forming efficiency compared to CD264 − MSCs (Madsen et al, 2020).…”
Section: Phenotypic Heterogeneity Of Senescent Mscsmentioning
confidence: 99%
“…The only significant difference identified was the higher expression of CD146 on the surface of BM-MSCs than on that of SV-MSCs. Previous findings in in vitro and animal models suggest that higher CD146 level on MSCs is associated with more plasticity, better ability for transendothelial migration but lower regenerative potential of the cells [ 29 , 30 ]. Further studies examining the human relevance of these observations need to be performed.…”
Section: Discussionmentioning
confidence: 99%